華麗緣中的愛玲女神——《樸廉紳士》、《半生緣》和進念舞臺改編探論: An Investigation of H. M. Pulham Esquire Half a Lifetime Love and Zuni Icosahedron’s Eighteen Springs
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":705,"3":"1":0,"9":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">“張愛玲”這個名字，在今天已成爲一個閃亮的符號。藉由媒體傳播，張愛玲其人其作，反覆見諸各選集和評傳，以至熒屏和舞臺。這個現象，到底帶來了甚麽啓示？本文的目的，便是以《半生緣》爲切入點，探討這個“張愛玲（改編/造神？）現象”。本文嘗試把張愛玲的《半生緣》、馬寬德的《樸廉紳士》（《半生緣》的寫作藍本）和香港劇團“進念ᆞ二十面體”的《半生緣》舞臺改编，置於一個互文脈絡中加以考察。論文第二部分，討論進念的舞臺改编如何藉著佈景、服装和音樂，製造一個去歷史的抽離時空，并把張愛玲的上海弄堂視角置换成一種當代的時間感知。第三部分藉著港臺兩地對此劇評價的分别，探討香港的劇作人和劇評人，如何改編和接受張愛玲。張愛玲既是象徵著現代性和都市生活的女神，同時亦是帶著悲憫的地母。第四部分是有關《半生緣》和《樸廉紳士》的互文思考，提出張愛玲對馬寬德的借用，紀録著張愛玲與世界文學同步的現代經驗。緬懷和追憶，是兩個作品互通的基調。 The name “Zhang Ailing” (Eileen Chang) has now become a shining symbol. The works and images of Chang repeatedly appear in various anthologies, critical biographies, and on screen and stage. What are the implications of this phenomenon? The aim of this paper is to investigate this “Zhang Ailing (adaptation/ deification?) phenomenon”, with her novel Half a Lifetime Love (Bansheng yuan) as the focus of examination. The paper discusses Zhang Ailing’s Half a Lifetime Love, John P. Marquand’ s H. M. Pulham Esquire (the structural source of Half a Lifetime Love) and the Hong Kong drama group Zuni Icosahedron’s Eighteen Springs (a stage adaptation of Half a Lifetime Love) in an inter-textual context. The second section of the paper analyzes how Zuni Icosahedron’s adaptation creates a de-historicized setting by its backdrop, costume and music, therely replacing the nongtang (lane) perspective of Zhang with a contemporary consciousness of time. The third section examines the differences in the reviews of this adaptation in Taiwan and Hong Kong, so as to understand how playwrights, directors and reviewers of Hong Kong adapt and receive Zhang. Zhang is not only a goddess symbolizing modernity and urban life, she is also an earth-mother with sympathy. The fourth section is a (re) consideration of the relationship between Half a Lifetime Love and H. M. Pulham Esquire, holding that Zhang’s appropriation of Marquand marks her modern experience, which is in synchronization with the West. Also, nostalgia and remembrance are the common themes between the two works. , journal=人文中國學報, author=何杏楓, year=2007, month=Sep., pages=175–213